Analysis of point difference established by winners and losers in games of badminton - Barreira, J.; Chiminazzo, J. G. C.; Fernandes, P. T. (International Journal of Performance Analysis in Sport, 2016)
The aim of this study was to analyze the point difference established at different phases of the game by the winners and losers in men's singles badminton matches. We analyzed 136 games from matches of the 2015 World Championship. From each game were collected the final result and the maximum point difference established by the players in each phase of the game. We considered from 0 to 7 points the first phase, from 8 to 14 the second phase and 15 to 21 the third phase of the game. We found that in all phases the winners had a superior point difference than the losers and this difference increased significantly over the course of the match. For all the players who were not ahead on the scoreboard in the first phase, 78% have lost the game. We found that one point ahead in the second and third phases was not enough for athletes to win the game. The winners had at least five points of difference to the opponent from the middle to the end of the game. The results presented are important to monitor the athlete's performance during the game and to readjust strategies based on point difference.